The predictors of whistleblowing intentions at UiTM Kedah / Shahriza Ilyana Ramli, Siti Norfazlina Yusoff, Azlyn Ahmad Zawawi - Ramli, Shahriza Ilyana; Yusoff, Siti Norfazlina; Ahmad Zawawi, Azlyn (Institute of Research Management & Innovation (IRMI), 2014)
Whistleblowing was a word created in 70s. In Malaysia, the act pertaining this matter has been enforced on 15 December 2010 by its name Whistle-blower Protection Act 2010, under Act 117. The need to establish this act is seen after a numbers of initiatives and programmes handled by government to uphold the public administration in Malaysia seems like not giving any impact. After all, the wrongdoings are still happened and it is at alarming stake. Basically, this act has been passed by parliament in the measurement taken against corruption cases which as one of the focus under second thrust of New Key Result Area (NKRA) which is to combat the corruption in Malaysia with the hope that indirectly, it will help attaining the first thrust of NKRA which is to eventually reduce the criminal rate in Malaysia. This paper is intended to investigate The Predictors of Whistle Blowing Intentions at UiTM Kedah. The research is conducted at Universiti Teknologi MARA, Kedah with the sample size of 80. There are three predictors were tested; retaliation, loyalty and culture of the organization. Pearson Correlation analysis is used to determine the relationships between these predictors and whistle blowing intentions. Meanwhile, the Regression analysis is used to investigate the most dominant factor among all. Thus, with this research it is hope that it would be a drive towards establishing ethical culture among public servant to blow the whistle if they found any wrongdoings happened.